2018
DOI: 10.1002/ejsp.2386
|View full text |Cite
|
Sign up to set email alerts
|

A dual‐process motivational model of attitudes towards vegetarians and vegans

Abstract: Vegetarians and vegans comprise a minority of most western populations. However, relatively little research has investigated the psychological foundations of attitudes towards this minority group. The following study employs a dual process model of intergroup attitudes to explore the motivational basis of non‐vegetarians' attitudes towards vegetarians and vegans. Participants were 1,326 individuals recruited through advertisements in a national newspaper in New Zealand. Non‐vegetarian participants first comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
59
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 37 publications
10
59
1
Order By: Relevance
“…Driven by motivations for social cohesion and resistance to change common practices, those higher on RWA are more likely to support and engage in traditional practices, including those harmful to animals (e.g., meat consumption), and to perceive vegetarianism and veganism as a threat to culture and family traditions Dhont et al, 2016;Monteiro, Pfeiler, Patterson, & Milburn, 2017). Furthermore, in line with Duckitt's (2001) Dual Process Motivational Model of ideology and prejudice (Duckitt & Sibley, 2010;Sibley & Duckitt, 2008), when tested simultaneously as predictors of prejudice towards vegetarians and vegans, RWA and SDO each uniquely account for part of the variance in these criterion variables (Judge & Wilson, 2019), and show differential relations with different beliefs about animals and vegetarianism (e.g., Dhont et al, 2016). Until recently, both SDO and RWA, widely considered the most important individual difference predictors of prejudice (Altemeyer, 1998;Hodson, MacInnis, & RETHINKING HUMAN-ANIMAL RELATIONS 10 Busseri, 2017), were only employed to study human-human prejudices (e.g., sexism, racism).…”
Section: Generalized Prejudice Social Dominance Authoritarianism Amentioning
confidence: 96%
“…Driven by motivations for social cohesion and resistance to change common practices, those higher on RWA are more likely to support and engage in traditional practices, including those harmful to animals (e.g., meat consumption), and to perceive vegetarianism and veganism as a threat to culture and family traditions Dhont et al, 2016;Monteiro, Pfeiler, Patterson, & Milburn, 2017). Furthermore, in line with Duckitt's (2001) Dual Process Motivational Model of ideology and prejudice (Duckitt & Sibley, 2010;Sibley & Duckitt, 2008), when tested simultaneously as predictors of prejudice towards vegetarians and vegans, RWA and SDO each uniquely account for part of the variance in these criterion variables (Judge & Wilson, 2019), and show differential relations with different beliefs about animals and vegetarianism (e.g., Dhont et al, 2016). Until recently, both SDO and RWA, widely considered the most important individual difference predictors of prejudice (Altemeyer, 1998;Hodson, MacInnis, & RETHINKING HUMAN-ANIMAL RELATIONS 10 Busseri, 2017), were only employed to study human-human prejudices (e.g., sexism, racism).…”
Section: Generalized Prejudice Social Dominance Authoritarianism Amentioning
confidence: 96%
“…Even though vegans/vegetarians are often regarded as a minority group, which leads to discrimination, or as a threat to the values and principles of the Western lifestyle [35,36], most often they encounter positive reactions from meat-eaters [37,38]. However, some studies show that omnivorous men have a more negative attitude towards vegetarians than omnivorous women (e.g., [37,39,40]). For instance, an analysis by Judge and Wilson [37] shows a main effect of sex, indicating that omnivorous men expressed significantly less positive attitudes towards vegetarians and vegans than female non-vegetarians.…”
Section: Gender-biased Perception Of Vegans/vegetariansmentioning
confidence: 99%
“…However, some studies show that omnivorous men have a more negative attitude towards vegetarians than omnivorous women (e.g., [37,39,40]). For instance, an analysis by Judge and Wilson [37] shows a main effect of sex, indicating that omnivorous men expressed significantly less positive attitudes towards vegetarians and vegans than female non-vegetarians. At the same time, men scored lower on the dominance and right-wing authoritarianism scale.…”
Section: Gender-biased Perception Of Vegans/vegetariansmentioning
confidence: 99%
“…The variety of human dietary types can not only be categorized according to different dietary groups but also affects the positive or negative attitudes of omnivores and vegetarians toward each other. To explore the attitudes of omnivores and vegetarians toward each other would contribute to other recent attempts to understand the basis of differences in attitudes between different dietary groups (e.g., Chin et al, 2002; Ruby and Heine, 2011; Minson and Monin, 2012; Ruby, 2012; Ruby et al, 2016; MacInnis and Hodson, 2017; Judge and Wilson, 2019) and to discuss how attitudes can be used to facilitate relationships between omnivores and vegetarians. With the aim of investigating the differences in attitudes between omnivores and vegetarians, the present research examined omnivores’ attitudes toward vegetarians and vegetarians’ attitudes toward omnivores in two Chinese samples.…”
Section: Introductionmentioning
confidence: 99%
“…As such, meat eaters were observed to report more negative attitudes toward vegetarians than to omnivores, and vegetarians themselves also reported negative experiences as a result of their vegetarianism (MacInnis and Hodson, 2017). In addition, a recent study revealed that omnivore participants from New Zealand treated vegetarians as deviant and dissident (Judge and Wilson, 2019). Third, from the perspective of vegaphobia, some omnivores may have a vegaphobic bias.…”
Section: Introductionmentioning
confidence: 99%